Effect of Haemodialysis on Mean Prothrombin Time and Activated Partial Thromboplastin Time in Patients of End Stage Renal Disease - Attika Khalid and Lubna Zafar (Journal of Rawalpindi Medical College, 2015)
Background: To determine mean prothrombin time and activated partial thromboplastin time in patients of end stage renal disease having normal baseline coagulation parameters after hemodialysis. Methods: In this cross sectional study 84 patients ,16-70 years of age, with end stage renal disease were selected. Prothrombin Time (PT) and Activated Partial Thromboplastin Time (APTT) were performed pre and post dialysis on venous blood samples of these patients. Results: Mean predialysis PT and APTT 13.33± 0.96 and 32.45± 1.87 seconds respectively A significant increase in the haemostatic parameters post dialysis was observed with mean PT and APTT 15.64±3.18 and 46.54±24.68 seconds respectively with a p-value of <0.001 for both parameters. Conclusion: Haemostatic parameters i.e prothrombin time and activated partial thromboplastin time are prolonged after haemodialysis in patients with end stage renal disease.